THE RELATIONSHIP OF KNOWLEDGE AND THE BEHAVIOR OF DENTAL POST GRADUATED STUDENTS REGARDING PERSONAL PROTECTIVE EQUIPMENT AT RSGM SARASWATI DENPASAR - Dwiastutik Listiantari; Ni Luh Gede Aris Maytadewi Negara; Agnes Ayu Biomi (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Coass Dental is one of the health workers who treat dental patients and is at risk of contracting or transmitting viruses and diseases. Knowledge of the use and disposal of PPE and good behavior is needed to minimize work accidents, Occupational Diseases and nosocomial infections. The purpose of this study was to determine the relationship betwehe knowledge and behavior of dental students regarding personal protective equipment at the Saraswati Oral and Dental Hospital, Denpasar. Material and Methods: The method used in this research is observational analytic with cross sectional approach. Total population of 50 teeth koas with sampling technique using probability sampling. The instruments used were PPE knowledge questionnaires and behavioral questionnaires on the use and disposal of PPE. Results and Discussions: Chi-square analysis (X2) showed no significant relationship between knowledge and behavior on the use and disposal of PPE with a value of 0.067 (p ≥ 0.05). Conclusion: Based on the results of the study, it was stated that there was no statistically significant relationship between knowledge and behavior of dental students regarding personal protective equipment at the Saraswati Oral and Dental Hospital, Denpasar.